Modern earthquake engineering : offshore and land-based structures - Jia, Junbo (Springer, 2017)
This book focuses on the application of earthquake engineering to offshore infrastructures. It covers a wide range of topics, from seismology to the seismic performance of arctic structures.
Keywords: Earthquake engineering.; Offshore structures.; Structural analysis (Engineering); elektronické knihy; electronic books